Cannabis and the developing brain - Melis, Miriam; Manzoni, Olivier (Academic Press, an imprint of Elsevier, 2022)
Marijuana is the most commonly used psychotropic drug in the United States, after alcohol. With the legalization and decriminalization of cannabis, momentum continues to build and propelled by the reduction of stigma associated to its consumption, there is growing concern regarding the long-term impact on brain function and behavior. Cannabis and the Developing Brain aims to provide comprehensive research on the effects of cannabis during neurodevelopment stages (i.e., perinatal and adolescent ages). This book introduces readers to vivo neural circuits, molecular and cellular mechanisms affected by cannabis exposure during three different temporal windows of brain vulnerability. Second, it offers a unique insight to shared neurobiological features of cannabinoid exposure during different developmental periods. Lastly, Cannabis and the Developing Brain determines the adverse impact of developmental cannabinoid exposure on specific cognition, emotion and behaviors. Reviews exposure effects on different areas and circuits of the brain Identifies effects of exposure at prenatal, perinatal, infant, and adolescent ages Includes cannabis interaction with known genetic and environmental risk factors Contains neurodevelopment and neuropsychiatric disorders associated with cannabis exposure--